Waktu dan Kemerahan Vulva Saat Inseminasi Buatan Merupakan Faktor Penentu Angka Kebuntingan Sapi di Sumatera Barat (TIME AND REDDISH SIGN OF VULVA DURINGARTIFICIAL INSEMINATION AS A DETERMINANT FACTORS ON CONCEPTION RATE OF COW IN WEST SUMATERA) - Udin, Zaituni; Rahim, Ferdinal; Hendri, Hendri; Yellita, Yulia (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
An experiment was conducted to evaluate determinant factors on conception rate of local and crossbreedcow at West Sumatera. There were 162 cows of four AI center at parity-0 to 4TH parity (P-4), inseminatedusing frozen semen of four different bulls (simental,brahman, limousine and Bali cattle). All fed similarityat four AI centers and location to observation of sign of estrus in high land and low land in West Sumatera.All data were analyzed using analyzed of variance in Randomized Block Design (RBD) in factorial as afactor A was time of inseminated; parity;sign of vulva,breed and two location as a replication. Resultsofthis study showed that there were no interaction between time of insemination, breed, parity and thereddish sign of vulva (P>0.05) on conception rate. On the contrary,there were significantly different(P>0.05) on conception rate by time of insemination. The highest conception rate wasfound at the end ofestrus 13–18 h (68.91%),local cow (71.82%), P-3 (67.19%) and reddish sign of vulva (74.25%). It wasconcluded that the effects,both inseminationtime and reddish sign of vulva might be the important factorto get the highest conception rate of the cows.
Keywords: time of insemination, parity, sign of vulva, parity, conception rate